2021
DOI: 10.3390/nano11113107
|View full text |Cite
|
Sign up to set email alerts
|

New Strategy for Inducing Surface Anisotropy in Polyimide Films for Nematics Orientation in Display Applications

Abstract: The operability of liquid crystal displays is strongly impacted by the orientation aspects of nematics, which in turn are affected by the alignment layer surface features. In this work, two polyimide (PI) structures are obtained based on a cycloaliphatic dianhydride and aromatic or aliphatic diamines with distinct flexibility. The attained PI films have high transmittance (T) for visible radiations, i.e., at 550 nm T > 80%. Here, a novel strategy for creating surface anisotropy in the samples that combines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…The operating principle of an Abbe refractometer arises from the phenomenon of refraction, and it computes the refractive index of the examined material by utilizing Snell’s law. The principal elements of this device are the monochromatic light source, the mirror, the prism system, and the focusing telescope [ 37 ]. The incident radiation travels via the double prism containing the sample with the condition of having an angle of incidence at the interface under the critical angle of total reflection.…”
Section: Optical Methods For Linear Birefringence Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The operating principle of an Abbe refractometer arises from the phenomenon of refraction, and it computes the refractive index of the examined material by utilizing Snell’s law. The principal elements of this device are the monochromatic light source, the mirror, the prism system, and the focusing telescope [ 37 ]. The incident radiation travels via the double prism containing the sample with the condition of having an angle of incidence at the interface under the critical angle of total reflection.…”
Section: Optical Methods For Linear Birefringence Evaluationmentioning
confidence: 99%
“…Another way to induce double refraction in PIs is based, as in the case of PVA, on mechanical deformation. In a recent study, two PI structures containing a common cycloaliphatic segment were surface-textured using a complex procedure to verify their applicability as orientation sheets for nematics in liquid crystal display devices [ 37 ]. The surface adaptation route involved stretching and/or rubbing.…”
Section: Optically Birefringent Polymer Materials and Their Applicationsmentioning
confidence: 99%
“…One category of polymers that best meets the described technical demands is represented by polyimides (PIs), which are acknowledged for their capacity to remain stable under heat, moisture, chemical substances, and radiation. The balance between the PI’s thermal, optical, morphological, and wettability characteristics can be adjusted by means of the chemical structure [ 11 , 12 ]. The literature shows that there are not many studies dealing with PI involvement in solar cell applications and they principally describe fully aromatic commercial structures (Kapton [ 13 ] or Upilex [ 14 ]), while others analyze certain aromatic non-commercial PIs [ 15 , 16 ], all being employed as flexible substrates.…”
Section: Introductionmentioning
confidence: 99%
“…The technique enables production of pre-defined patterns via raster or vector methods but is constrained to a small surface area. Mechanical abrasion can be performed by scratching the polymer film with materials of distinct toughness, such as textile materials [32] or sandpaper [33], resulting unidirectional micro-grooves and surface anisotropy. In a previous piece of work, we demonstrated that the size and flexibility of the textile fiber is affecting the resulted traces uniformity and dimensions [34].…”
Section: Introductionmentioning
confidence: 99%